Equine Erythrocyte Lysed Exposed to T-Butyl Hydroperoxide as a Model to Study the Oxidative Stress Caused by Exercise using a Chemiluminescence Assay (Global Journal of Medical Research, 2017)
The present investigation was carried out to determine the presence of oxidative alterations in the horses erythrocyte membrane during a high intensity exercise test. The degree of peroxidation was estimated by chemiluminescence using a suspension of lysed erythrocytes incubated with t-butyl hydroperoxide (t-BHP). Differences were observed in the total values of chemiluminescence throughout the exercise routine, with higher values of light emission obtained with the animal at rest in relation to those observed during and after exercise.The conclusions of this study are the existence of changes in the erythrocyte membranes of the horses exposed to physical exertion, probably associated with the release of ROS caused by the exercise and that the determination of chemiluminescence in suspension of lysates erythrocyte is a sensitive assay applied to detect the existence of oxidative stress associated to physical exercise.
Keywords: oxidative stress; exercise; chemilumine-scence; erythrocyte; tert-butyl hydroperoxide